2016
DOI: 10.1002/ps.4420
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of fabricated mesoporous alumina nanoparticles against root rot disease of tomato caused by Fusarium oxysporium

Abstract: Our study demonstrated the possible use of cylindrically cubic MAS nanoparticles as an effective alternative for the control of Fusarium root rot in tomato. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(31 citation statements)
references
References 22 publications
3
28
0
Order By: Relevance
“…To date, TiO 2 , CuO (Hao et al, 2017(Hao et al, , 2019Liu et al, 2017), Zn, ZnO (Xue et al, 2014;Antonoglou et al, 2018;Sun et al, 2018), carbon nanomaterials (Chen et al, 2014(Chen et al, , 2016b, Al, and Si nanoparticles (Park H.J. et al, 2006;Shenashen et al, 2017) have been reported to display toxicity toward phytopathogenic bacteria and fungi, decreasing the disease incidence. Recently, our group also found that graphene oxide silver nanoparticle (GO-AgNP) nanocomposites can suppress the development of hyphae, showing a significant effect in controlling leaf spot disease from Fusarium graminearum (Chen et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…To date, TiO 2 , CuO (Hao et al, 2017(Hao et al, , 2019Liu et al, 2017), Zn, ZnO (Xue et al, 2014;Antonoglou et al, 2018;Sun et al, 2018), carbon nanomaterials (Chen et al, 2014(Chen et al, , 2016b, Al, and Si nanoparticles (Park H.J. et al, 2006;Shenashen et al, 2017) have been reported to display toxicity toward phytopathogenic bacteria and fungi, decreasing the disease incidence. Recently, our group also found that graphene oxide silver nanoparticle (GO-AgNP) nanocomposites can suppress the development of hyphae, showing a significant effect in controlling leaf spot disease from Fusarium graminearum (Chen et al, 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an essential need to adopt alternative approaches for the management of pathogens. An adequate approach that is being actively investigated involves NPs, such as metal oxides, which are used to control soilborne fungi (Shenashen et al, 2017).…”
mentioning
confidence: 99%
“…Strong membrane-disruptive properties associated to intracellular effects have already been reported for alumina nanoparticles acting on Candida yeasts [52]. In addition, mesoporous alumina inhibits the growth of the phytopathogen Fusarium oxysporium in vitro and in infected tomato plants [53]. The material obtained by Jalal and co-workers was active on several Candida species and HRTEM revealed that the nanoparticle anchoring occurs on the cell surface and that subsequent internalization of minor nanostructures in the yeast cells leads to the rupture of the wall and cell membranes and, consequently, to cell death.…”
Section: Discussionmentioning
confidence: 85%